STRUKTUR PENYAJIAN TARI JEPIN TEMBUNG PENDEK KARYA M. YUSUF DAHYANI - Canigia, Diego Antoni; Ismunandar, Ismunandar; Silaban, Chiristianly Yeri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aspects of Jepin Tembung Pendek dance by M. Yusuf Dahyani has been the researcher’s interest to explore and analyze through this research. The aim of this study is to define the structure of the dance performance. This research was conducted using a descriptive method. Through observation, interviews, and documentation techniques the data were collected in the form of presentation structure of Jepin Tembung Pendek dance that comprises 3 main parts of dance (beginning, middle, and end) from the informants M Yusuf Dahyani and Anwar Dzafar. Based on the results of the interview, the dance was debuted in the 1930s. The previous basic movement of dance was created by Mr Unggal Jais from Teluk Pak Kedai. At that time, dance had not undergone any change in the components of motion, music, and costumes. The supporting elements of the dance are music, costumes, and attributes. Becoming a piece of the cultural richness, the dance of Jepin Tembung Pendek must be maintained to bring it to the next generations. Keywords: Presentation Structure, Jepin Tembung Pendek Dance by M.Yusuf Dahyani